(untitled) (Bioagro, 2024)
Species of the genus Fusarium are the main cause of root rot in bean crops, resulting in yield losses of up to 50%. Synthetic fungicides are the primary tools for their control; however, they cause environmental damage. The objective of this study was to evaluate the effect of extracts from A. ochroleuca on Fusarium spp. under in vitro conditions. During the spring-summer 2022 growing season, plants exhibiting symptoms of wilting and vascular browning were collected. The isolated fungi were purified through monosporic cultures and hyphal tip techniques, and their morphological characteristics were characterized. To determine growth inhibition, a poisoned medium methodology was employed, evaluating two concentrations of extracts (13% and 23%) in both ethanol and aqueous mediums. The obtained isolates corresponded to the morphological characteristics of Fusarium. The extract volumes that showed 100% inhibition were the 23% concentration in both ethanol and aqueous mediums. The 13% ethanol extract exhibited inhibition ranging from 29% to 62% between the first and tenth day of incubation. The 13% aqueous extract displayed inhibition ranging from 25% to 43%. The Argemone ochroleuca extract demonstrates antifungal properties against Fusarium spp. isolated from beans.